(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Electrical or insulation failure is usually accompanied by two major events among others; production of acoustic pulses (sound) and an increase in temperature owing to heating. These lead to costly energy dissipation. Distribution boards are elementary necessities in any electrical wiring but overheating at the junctions can result in serious energy loss and eventual fire outbreak. There are several methods and techniques used in monitoring and assessing the state of power equipment and components in the electricity network. One of such techniques is Infrared thermography (IRT). An average temperature of 92.4Â°C and 33.7Â°C were recorded on the three-phase distribution board for the building during the peak and off-peak periods respectively. The inspection of the distribution boards in the Physics Department building of Ahmadu Bello University, Zaria, using thermal imaging camera, revealed excessive heating at the three-phase distribution board during peak hours, leading to Ohmic loss. The dissipated energy during the peak period ranges from 665 W/m2 to 1.5 kW/m2. The heating resulted in an average energy loss of about 1 kW/m2. The energy loss at the junctions may have, among other factors, contributed to the high electricity billing at the university.